2012
DOI: 10.1002/aehe.3705
|View full text |Cite
|
Sign up to set email alerts
|

Table of Contents

Abstract: IntroductionSituating American Indian and Alaska Native Higher Education in Larger ContextsHistorical Background of American Indian and Alaska Native Higher EducationOverview of the MonographFraming the CoversationTribal Nation BuildingHigher Education Toward Nation BuildingConclusionPostsecondary Access for Indigenous StudentsPostsecondary Aspirations, High School Completion, and Academic PreparationAccelerated Learning OpportunitiesCollege Entrance ExaminationsEconomic Conditions and Paying for CollegeThe Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Additional studies that investigated possible causes for the high college dropout rates identified poor preparatory education and lack of community role models as factors that contribute to poor performance in higher education (Brayboy, Fann, Castagno, & Solyom, 2012). Given the scope of V/RA in the United States, it is important to explore its impact among all populations-including underrepresented ethno-racial minority youth such as AI/ ANs-and contexts, such as academic performance.…”
Section: Ai/an Educational Experiences and Outcomesmentioning
confidence: 99%
“…Additional studies that investigated possible causes for the high college dropout rates identified poor preparatory education and lack of community role models as factors that contribute to poor performance in higher education (Brayboy, Fann, Castagno, & Solyom, 2012). Given the scope of V/RA in the United States, it is important to explore its impact among all populations-including underrepresented ethno-racial minority youth such as AI/ ANs-and contexts, such as academic performance.…”
Section: Ai/an Educational Experiences and Outcomesmentioning
confidence: 99%
“…In addition to low enrollment, high rates of college dropout among AI students throughout the United States have been well documented (Braxton, Brier, & Steele, 2007; Flynn et al, 2012). According to Brayboy, Fann, Castagno, and Solyom (2012), inadequate preparatory education on tribal lands and lack of community role models are responsible for AI students’ limited success in predominantly White higher education. Similarly, Flynn, Duncan, and Evenson (2013) found poor postsecondary outcome expectations and low levels of career self-efficacy affect AIs who receive secondary education on tribal lands.…”
Section: Educational Achievementmentioning
confidence: 99%
“…Studies focused on Native Americans in higher education rarely, if ever, mention the academic library (Brayboy et al, 2012;Carney, 1999;Conroy, 2013;Huffman, 2008Huffman, , 2010Oosahwe, 2008;Reyhner & Eder, 2007;Tierney, 1992). One exception is Garrod and Larimore's (1997) study which included students' fond descriptions of their early library experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The university continues to rank high nationally on degrees conferred on Native American students (Top Native American, 2014). However, as administrators at other institutions have noted, retaining the majority of Native American students both within PWIs and in Tribal Colleges remains an unrealized institutional goal (Belgarde & LoRé, 2007;Brayboy, Fann, Castagno, & Solyom, 2012). At OSU, the firstyear retention rate and six-year graduation rate of full-time freshmen Native students, as well as other racial/ethnic groups, still lags behind those of White students (Oklahoma State University, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation